Functional Profile of Antigen Specific CD4(+) T Cells in the Immune Response to Phospholipase A1 Allergen from Polybia paulista Venom - Fernandes, Luís Gustavo Romani (Toxins (Basel), 2020)
Insect venom can cause systemic allergic reactions, including anaphylaxis. Improvements in diagnosis and venom immunotherapy (VIT) are based on a better understanding of an immunological response triggered by venom allergens. Previously, we demonstrated that the recombinant phospholipase A1 (rPoly p 1) from Polybia paulista wasp venom induces specific IgE and IgG antibodies in sensitized mice, which recognized the native allergen. Here, we addressed the T cell immune response of rPoly p 1-sensitized BALB/c mice. Cultures of splenocytes were stimulated with Polybia paulista venom extract and the proliferation of CD8(+) and CD4(+) T cells and the frequency of T regulatory cells (Tregs) populations were assessed by flow cytometry. Cytokines were quantified in cell culture supernatants in ELISA assays. The in vitro stimulation of T cells from sensitized mice induces a significant proliferation of CD4(+) T cells, but not of CD8(+) T cells. The cytokine pattern showed a high concentration of IFN-γ and IL-6, and no significant differences to IL-4, IL-1β and TGF-β1 production. In addition, the rPoly p 1 group showed a pronounced expansion of CD4(+)CD25(+)FoxP3(+) and CD4(+)CD25(-)FoxP3(+) Tregs. rPoly p 1 sensitization induces a Th1/Treg profile in CD4(+) T cell subset, suggesting its potential use in wasp venom immunotherapy.